Adaptación modular a instituciones educativas para el mejoramiento del aprendizaje en Cartagena (2020)
The student environment for years has been the same, in Cartagena de Indias the school environment in the standard disciplines such as mathematics, physics, chemistry, among others, the panorama is standard, unlike other disciplines such as artistic, physical education and other subjects. that are not contemplated in the educational planes of the educational institutions of the city, although there are schools that include there are others that do not, and usually the less favored are the public institutions, this city being recognized for its cultural and artistic wealth brings that knowledge to all its citizens. Through an exhaustive search it is found that Cartagena does not have teams where its citizens develop their cultural and artistic knowledge and knowledge, and in the area where they should have applied it is not, it should be in institutions, where students and parents of these find spaces in which to develop these activities, generating knowledge and cultural and artistic development, giving citizens opportunities to learn about their culture, appropriate it and have new learning methods, from children to adults.